Сomponents of the post-Soviet space Korean diaspora construct - Кутулуков, Ш.П. П. (Journal of Oriental Studies, 2017)
This article is an attempt to analyze the CIS subethnic group Korean Koryo Saram and the phenomenon investigation within the constructivist approach. By means of “site of commemoration” concept there have been revealed the main points of Korean ethnic group commemoration. The features of the Korean diaspora have been outlined and framework components of the Koryo Saram and the Korean Peninsula collective memory have been considered along with identification of their main complementary characteristics. Also there have been defined the role of Korean language (Koryo-Mar) and written into the structure of sub-ethnic constructs Koryo Saram.